(untitled) (Comprehensive Journal of Science, 2026)
This research aims to study the water sources of Leptis Magna and reveal their role in the city’s origins and urban development during ancient times, particularly the Roman period, focusing on the nature of these sources and their management mechanisms. The research also seeks to highlight the integrated nature of the city’s water system, considering the specific environmental and climatic conditions of the region. The research employed a descriptive-analytical approach, documenting and studying water infrastructure, such as dams built on wadis (valleys), most notably the Wadi Lebda and Wadi Kaam dams, as well as reservoirs, cisterns, and wells within the city. This was complemented by an analysis of archaeological and architectural evidence, historical sources, and modern archaeological studies. A comparative approach was also utilized, where appropriate, by comparing the water system of Leptis Magna with those of other Roman cities in North Africa. The research concluded that Leptis Magna relied on a comprehensive, multi-source water system. This system was based on controlling seasonal wadi water through dams, storing water in reservoirs and cisterns, and utilizing groundwater through wells. The results also showed that this system reflected an advanced level of engineering planning and water management, and directly contributed to supporting public facilities, particularly baths and fountains, as well as meeting the daily needs of the population. The research concludes that the water management system in Leptis Magna was a fundamental element of urban planning and the continuity of urban life, and that the city’s success in utilizing its water resources contributed to its prosperity and prominence among the cities of Roman North Africa. The research recommends the continuation of specialized archaeological studies to document water infrastructure and preserve this heritage.